2009
DOI: 10.1021/jm8009469
|View full text |Cite
|
Sign up to set email alerts
|

Indene-Based Scaffolds. 2. An Indole−Indene Switch: Discovery of Novel Indenylsulfonamides as 5-HT6 Serotonin Receptor Agonists

Abstract: Scaffold selection involving an indole-to-indene core change led to the discovery of a series of indenylsulfonamides that act as 5-HT6 serotonin receptor agonists. The variety of the targeted ligands and their synthetic complexity required multistep synthetic approaches. The novel indenylsulfonamides exhibited variable binding affinities for the 5-HT6 receptor, and the in vitro primary binding profiles of the preferred compounds revealed them to be 5-HT6 receptor agonists with Ki values > or =4.5 nM. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
(101 reference statements)
0
33
0
Order By: Relevance
“…61,62 The hit compound 21 behaved as a full agonist of 5-HT 6 R, featuring strong binding affinity (K i = 4.5 nM; EC 50 = 0.9 nM). Moreover, this compound was highly selective over the adrenergic α receptors (IC 50 > 1000 nM) and the serotonergic 5-HT 1A and 5-HT 2C R (IC 50 > 1000 nM).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…61,62 The hit compound 21 behaved as a full agonist of 5-HT 6 R, featuring strong binding affinity (K i = 4.5 nM; EC 50 = 0.9 nM). Moreover, this compound was highly selective over the adrenergic α receptors (IC 50 > 1000 nM) and the serotonergic 5-HT 1A and 5-HT 2C R (IC 50 > 1000 nM).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…In addition, indene-based structures are a source of bioactive compounds in drug discovery and development [1018]. The routes to access multiply substituted indenes with at least two different functional groups (FGs) are generally complex, and the synthetic approaches leading to these compounds lag behind those for heteroaromatic systems, e.g., indoles, being limited as it is by the scarce knowledge of indene chemistry in comparison with heterocyclic chemistry [3,1722].…”
Section: Introductionmentioning
confidence: 99%
“…During the course of our studies on indene-based ligands of general type 1 with biological effects on the central nervous system, we found that different stepwise synthetic routes could be applied to inden-5-amines 2 bearing a disubstituted N , N -aminoethyl side arm at the indene 3-position [1718]. After analyzing reasonable synthetic routes to the [3-(aminoethyl)inden-5-yl)]amine intermediates 2 starting from substituted indan-1-one 5 , route A was chosen as the most suitable way of functionalizing the 5-position of the indene, e.g., by changing the aryl(heteroaryl) structural motif of a sulfonamide moiety (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations